2006
DOI: 10.1093/jhmas/jrj046
|View full text |Cite
|
Sign up to set email alerts
|

Infection, Contagion, and Public Health in Late Medieval and Early Modern German Imperial Towns

Abstract: From today's point of view, the concepts of "miasma" and "contagion" appear to be two mutually exclusive perceptions of the spread of epidemic diseases, and quite a number of historians have tried to discuss the history of public health and epidemic diseases in terms of a progression from the miasmic to the contagionist concept. More detailed local studies, however, indicate how extremely misleading it may be to separate such medical concepts and ideas from their actual historical context. The article presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…This may be related to the fact that, unlike Spencer, Smith was concerned with the infectious aspects of disease, rather than with its contagious effects in society. While in previous centuries infection and contagion were equally used to describe diseases (Kinzelbach ), historian François Delaporte () has showed that these two medical schools of the 19th century develop two different views of public health. Following him, while contagionists viewed diseases as spread by contact and recommended creating boundaries, infectionists returned to the origin point of an epidemic and aimed to restore the circulation of life around that place by cleaning habitats or killing animals.…”
Section: William Robertson Smith and Bovine Tuberculosis: Participatimentioning
confidence: 99%
“…This may be related to the fact that, unlike Spencer, Smith was concerned with the infectious aspects of disease, rather than with its contagious effects in society. While in previous centuries infection and contagion were equally used to describe diseases (Kinzelbach ), historian François Delaporte () has showed that these two medical schools of the 19th century develop two different views of public health. Following him, while contagionists viewed diseases as spread by contact and recommended creating boundaries, infectionists returned to the origin point of an epidemic and aimed to restore the circulation of life around that place by cleaning habitats or killing animals.…”
Section: William Robertson Smith and Bovine Tuberculosis: Participatimentioning
confidence: 99%
“…23 February 2009). Others saw the wilderness itself as hazardous for humans, with disease-carrying insects, polio-infested water, and lurking snakes, evoking a deeply rooted, Euro-American cultural model that associates swampland with ill health (Kinzelbach, 2006). In a more passive role, the wetlands occasionally provided shelter for homeless people or mischievous teenagers, who also posed a threat to passers-by.…”
Section: 'The Endangered Species Is People'mentioning
confidence: 99%
“…The reference to the crisis is very precise in the following passage: ''The word 'panic' has been used, like the word 'cholera', as if something in the air occasioned it, or it arose from some cause over which mankind has no power; and as naturally do merchants calculate on periodical panics as physicians do on cholera appearing in the fruit season (Anonymous 1, 1836, p. 16). Overstone also explicitly referred to the return of periods of excitement and of distress, comparing the consequences of the state of currency with that of the atmosphere: 50 On the medical explanations, see, e.g., Nutton (1990,) Hamlin (1992, and Kinzelbach (2006).…”
Section: Bad Atmosphere Vs Contagionmentioning
confidence: 99%